Performing oaths in classical Greek drama - Fletcher, Judith (Cambridge University Press, 2012)
"Oaths were ubiquitous rituals in ancient Athenian legal, commercial, civic and international spheres. Their importance is reflected by the fact that much of surviving Greek drama features a formal oath sworn before the audience. This is the first comprehensive study of that phenomenon. The book explores how the oath can mark or structure a dramatic plot, at times compelling characters like Euripides' Hippolytus to act contrary to their best interests. It demonstrates how dramatic oaths resonate with oath rituals familiar to the Athenian audiences. Aristophanes' Lysistrata and her accomplices, for example, swear an oath that blends protocols of international treaties with priestesses' vows of sexual abstinence. By employing the principles of Speech Act theory, this book examines how the performative power of the dramatic oath can mirror the status quo, but also disturb categories of gender, social status and civic identity in ways that redistribute and confound social authority"--